2017
DOI: 10.1016/j.sapharm.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Quality improvement practices to institutionalize supply chain best practices for iCCM: Evidence from Rwanda and Malawi

Abstract: BackgroundSupply chain bottlenecks that prevent community health workers (CHWs) from accessing essential medicines significantly increase under-5 child mortality, particularly in poor and rural areas.ObjectiveUsing implementation research, interventions aimed at improving supply chain practices and access to medicines were tested in Malawi and Rwanda. These interventions included simple demand-based resupply procedures, using mobile technology and traditional methods for communication, and multilevel, performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 13 publications
1
32
0
Order By: Relevance
“…Furthermore the use of WhatsApp® and mobile technology greatly improved our outcomes by improving the timeliness of order delivery. Another study has had similar findings using short message service [16].…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Furthermore the use of WhatsApp® and mobile technology greatly improved our outcomes by improving the timeliness of order delivery. Another study has had similar findings using short message service [16].…”
Section: Discussionmentioning
confidence: 52%
“…Our end goal is to sustain high performance (quality service provision) with supervision visits slowly removed due to cost. It will be important to assess sustainability given that a similar study found that sites revert back to baseline performance once interventions are discontinued [16].…”
Section: Discussionmentioning
confidence: 99%
“…The MoH of Rwanda together with its implementing partners developed tools for improved forecasting of community level demand of medical supplies to strengthen the PSM systems. The tools consisted of improved versions of paper-based resupply calculators and improved communication approaches designed by quality improvement teams [24,36]. In Malawi, similar efforts led to countrywide adoption of cStock, a simple mHealth reporting and resupply system that led to improvements in communication between the Health Surveillance Assistants (HSAs) and their resupply points.…”
Section: Tools For Improved Procurement Supply Chain Managementmentioning
confidence: 99%
“…In Malawi, similar efforts led to countrywide adoption of cStock, a simple mHealth reporting and resupply system that led to improvements in communication between the Health Surveillance Assistants (HSAs) and their resupply points. The application is reported to improve visualization of iCCM drug stocks at the district and central levels of the MoH through alert systems which enable supply chain managers to respond on a timely basis [36]. The Mozambique MoH together with its implementing partners are scaling up a digital community health system, called upSCALE, that enables supervisors to monitor medicine stokes by providing real-time data visualization [37].…”
Section: Tools For Improved Procurement Supply Chain Managementmentioning
confidence: 99%
See 1 more Smart Citation